Intraventricular Hemorrhage in Term Neonates: Sources, Severity and Outcome - AFSHARKHAS, Ladan; KHALESSI, Nasrin; KARIMI PANAH, Mohammad (Iranian Journal of Child Neurology, 2015)
How to Cite This Article: Afsharkhas L, Khalessi N, Karimi Panah M. Intraventricular Hemorrhage in Term Neonates: Sources, Severity and Outcome. Iran J Child Neurol. Summer 2015;9(3):34-39. Abstract Objective Intraventricular hemorrhage (IVH) occurs in preterm infants; however, the occurrence of this event is less frequent in term neonates. The present study evaluated clinical characteristics, pathophysiological features, and early outcome of term neonates with IVH in a referral neonatal center in Iran. Materials & Methods This study was performed on 30 full-term neonates admitted to the Neonatal Intensive Care Unit (NICU) of Ali-Asghar Hospital, Tehran, Iran between March 2005 and April 2011. IVH was diagnosed using cranial ultrasonography, or brain magnetic resonance imaging (MRI). Results The mean age at onset of symptoms was 3.9 days. Seizure was the commonest clinical symptoms followed by poor feeding and fever. The sources of bleeding in the brain were choroid plexus (60%), germinal matrix (20%) and parenchyma (6.7%). Severity of bleeding included 33.3% grade I, 30.0% grade II, 36.7% grade III to IV. Fifteen (50%) cases had coagulopathy. Twenty-five (83.3%) cases were discharged with a good condition, three (10%) cases were referred to surgical ward and two cases (6.7%) died in NICU. Conclusion The main source of IVH in term neonates is choroid plexus; the most common clinical symptoms include seizure and poor feeding, and one-third of IVH events are graded as III to IV. Most affected neonates are discharged from NICU without CNS complication, about 10% need to refer to surgical interventions, and death was occurred in a few of neonates.